Prolonged Impairment of Immunological Memory After Anti-CD20 Treatment in Pediatric Idiopathic Nephrotic Syndrome - Colucci, Manuela; Carsetti, Rita; Serafinelli, Jessica; Rocca, Salvatore; Massella, Laura; Gargiulo, Antonio; Lo Russo, Anna; Capponi, Claudia; Cotugno, Nicola; Porzio, Ottavia; Onetti Muda, Andrea; Palma, Paolo; et al. (Frontiers in Immunology, 2019)
Anti-CD20 therapy is effective in idiopathic nephrotic syndrome (INS). However, transient or sustained hypogammaglobulinemia predisposing to an increased risk of infectious diseases can follow treatment in some patients. We analyzed the long-term effects of anti-CD20 therapy on immunological memory in 27 frequently-relapsing/steroid-dependent INS pediatric patients after more than 4 years from the first and at least 2 years from the last anti-CD20 infusion. Twenty-one INS children, never treated with anti-CD20 and under an intense oral immunosuppression with prednisone, mycophenolate mofetil, and calcineurin inhibitors were also included as control group. Levels of circulating B-cell subpopulations, total serum immunoglobulins and IgG and memory B cells directed against hepatitis B virus (HBV) and tetanus were determined and correlated with clinical characteristics. Nine patients never relapsed after more than 2 years from the last anti-CD20 administration (5 after the first, 3 after the second, and 1 after the fifth infusion). At last follow-up, most patients showed a complete recovery and normalization of total (27/27), transitional (27/27), and mature-naïve B cells (25/27). However, a sustained and significant reduction of total memory (20/27) and switched memory (21/27) B cells was found in most patients. 11/27 patients showed hypogammaglobulinemia at last follow-up and, among these, four presented with a severe hypogammaglobulinemia (IgG < 160 mg/dl). In contrast, no patient in the control group developed a severe hypogammaglobulinemia. Age at the time of first anti-CD20 administration was positively associated with IgG levels at last follow-up (p = 0.008); accordingly, younger patients had an increased risk of hypogammaglobulinemia (p = 0.006). Furthermore, severe hypogammaglobulinemia and delayed switched memory B-cell reconstitution were more frequent in non-relapsing patients. Reduced IgG levels against HBV and tetanus were observed at baseline and further declined at last follow-up. Antigen-specific memory B-cells were induced by re-immunization, but specific IgG titers remained low. In conclusion, anti-CD20 therapy can be disease-modifying in some INS patients. However, a prolonged impairment of immunological memory occurs frequently, independently from the number of anti-CD20 infusions, particularly in younger patients. Re-immunization may be necessary in these patients.